The Effect of Human Resources Competence, Application of Local Government Accounting Systems, and Internal Control Systems on the Quality of Local Government Financial Reports - Ali Imransyah; M. Ardiansyah Syam; Syahril Djaddang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research was conducted to determine the factors that effect the quality of local government financial reports. The factors were "the effect of human resources competence, the application of the regional government accounting system, and the internal control systems on the quality of theWest Bandung district government financial report with the utilization of accounting information technology as moderation variable". The population in this research are employees of the regional work unit (SKPD) in West Bandung district. The saturation sampling technique used in this study was 63 SKPD staff. The data collection in this study used a questionnaire. Data were processed using multiple linear regression analysis. The results of hypothesis testing is the human absorption compentcy, the application of government accounting systems, utilization information technology, and internal control systems partially has a positive effect on the quality of the financial statements of the Government ofWest Bandung district.